1977
DOI: 10.1128/aem.33.5.1225-1228.1977
|View full text |Cite
|
Sign up to set email alerts
|

Use of nuclepore filters for counting bacteria by fluorescence microscopy

Abstract: Nuclepore filters are better than cellulose filters for the direct counting of bacteria because they have uniform pore size and a flat surface that retains all of the bacteria on top of the filter. Although cellulose filters also retain all of the bacteria, many are trapped inside the filter where they cannot be counted. Before use, the Nuclepore filters must be dyed with irgalan black to eliminate autofluorescence. Direct counts of bacteria in lake and ocean waters are twice as high with Nuclepore filters as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
1,166
1
26

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,920 publications
(1,223 citation statements)
references
References 10 publications
6
1,166
1
26
Order By: Relevance
“…These forms passed through a 1-p,m filter and were the principal food for the cladocerans in the 1-p,m-filtrate treatment. The average volume of planktonic bacterial cells is generally 0.05-0.10 p,m 3 (Ferguson and Rublee 1976, Bowden 1977, Hobbie et al 1977, Watson et al 1977, Zimmerman 1977. The biomass of free bacteria available to zooplankton for the different experiments can be calculated by assuming a cell density of 1.07 g/mL, a dryto wet-mass ratio of0.23, and a carbon to dry-mass ratio of0.5 (Bowden 1977, Watson et al 1977.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These forms passed through a 1-p,m filter and were the principal food for the cladocerans in the 1-p,m-filtrate treatment. The average volume of planktonic bacterial cells is generally 0.05-0.10 p,m 3 (Ferguson and Rublee 1976, Bowden 1977, Hobbie et al 1977, Watson et al 1977, Zimmerman 1977. The biomass of free bacteria available to zooplankton for the different experiments can be calculated by assuming a cell density of 1.07 g/mL, a dryto wet-mass ratio of0.23, and a carbon to dry-mass ratio of0.5 (Bowden 1977, Watson et al 1977.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of lake and pond carbon budgets suggest that zooplankton obtain a substantial proportion of their carbon from detritus pathways via bacteria (Wetzel 1975:611-613). Recent advances in methodology have confirmed that bacteria are both numerically abundant (Hobbie et al 1977, Watson et al 1977, Hobbie 1979, Porter and Feig 1980 and significant producers of biomass in the plankton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the laboratory, the bacterial concentration of sample water was determined by the acridine orange direct count method (Hobbie et al 1977) using an epifluorescence microscope (Olympus BH-2; Olympus Optical Co. Ltd., Tokyo). Each 100 p1 of sample water was filtered through a Nuclepore 0.2 pm filter, and bacteria retained on the filter were stained.…”
Section: Methodsmentioning
confidence: 99%
“…Subsamples of epiphyton, periphyton, and biofilm scrapes were kept for heterotroph and autotroph abundance estimates. Known volumes of epiphyton, periphyton, or biofilms were stained with either DAPI (4′,6-diamidino-2-phenylindole) for bacteria (Hobbie, Daley, & Jasper, 1977), or labeled lectin (fluorescien-labeled wheat germ agglutinin) for fungal counts (e.g., Wanchoo, Lewis, & Keyhani, 2009). Heterotrophs were counted under a microscope at 40× using epifluorescence, and autotrophs were counted using standard light microscopy at 40× magnification.…”
Section: Me Thodsmentioning
confidence: 99%